Variation in word formation in situations of language contact: The case of Cappadocian Greek. (May 2016) - Melissaropoulou, Dimitra
Abstract: This paper deals with variation in word-formation, i.e. derivational prefixation and suffixation, in situations of language contact and uses as a starting point dialectal innovations attested in Cappadocian Greek. The analysis involves both social and linguistic explanatory parameters, in order to offer further insights into contact-induced morphological change. Our data show that a unified account, whether primarily intra-linguistic or primarily extra-linguistic, cannot provide an adequate overall interpretation of the phenomena we investigate. Only a combined account, which addresses both internal and external developments, offers a perspective wide enough to offer an adequate explanation for variation in word-formation patterns in language contact situations. Moreover, we attempt to account for morphological subcomponents that are to varying degrees susceptible to contact-induced change. Our study thereby provides further support, derived this time from the domain of word-formation, for the claim that change involves two factors. These are, first, a small typological distance between subsystems in contact and, second, the relative markedness or status of the structures involved, which together may, while not actually of themselves causing change, still facilitate or enhance it, a phenomenon which in different circumstances (language-pairs) would be less likely to occur. Highlights: Address variation in derivational prefixation and suffixation in situations of language contact. Dialectal innovations are treated in terms of both social and linguistic explanatory parameters. Combinatorial accounts offer the most plausible explanations. Small typological distance and markedness may facilitate an otherwise less likely linguistic change.